The Open Window: Domestic Landscapes in Willa Cather’s My Antonia and Sapphira and the Slave Girl - Quantic, Diane Dufva (American Studies, 2002)
The Open Window: Domestic Landscapes in Willa Cather’s My Antonia and Sapphira and the Slave Girl